Cerebrospinal fluid rhinorrhoea: an overview of endoscopic multilayer repair - Shoeb, Mohammed; Mhashal, Shashikant; Gite, Vinod; Bhargava, Samir (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: A cerebrospinal fluid (CSF) rhinorrhoea occurs when there is communication between the subarachnoid space and the nasal cavity. CSF rhinorrhoea commonly occurs following head trauma (fronto-basal skull fractures), as a result of intracranial surgery or spontaneously. The aim of our article was to emphasize the importance of endonasal endoscopic surgery using multilayer autograft technique. Methods: A total of 08 cases of CSF rhinorrhoea were treated. A retrospective study was undertaken to analyze the characteristics of 08 patients. After detailed otorhinolaryngoscopic examination, diagnostic nasal endoscopy and radiological evaluation by CT and MRI, all underwent endonasal endoscopic surgery. This article reviews the causes, diagnosis and treatment of CSF leakage of cases done with a 0 degree 4 mm sinoscope using fascia lata septal cartilage and fat as a graft material. Results: The defects as large as 1.5 cm could be safely treated with this technique. The overall success rate of endoscopic repair for CSF rhinorrhoea has been 100%. Conclusions: Endonasal approach is less morbid compared with external approach. Endoscopic surgery gives better visualization.